Broadband Internet and the Stock Market Investments of Individual Investors - Hvide, Hans K.,Meling, Tom G.,Mogstad, Magne,Vestad, Ola Lotherington (National Bureau of Economic Research, 2022)
We study the effects of broadband internet use on the investment decisions of individual investors. A public program in Norway provides plausibly exogenous variation in internet use. Our instrumental variables estimates show that internet use causes a substantial increase in stock market participation, driven primarily by increased fund ownership. Existing investors tilt their portfolios towards funds, thereby obtaining more diversified portfolios and higher Sharpe ratios, and do not increase their trading activity in stocks. Overall, access to high-speed internet seems to spur a
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Anlageverhalten; Internet; Private Finanzplanung; Portfolio-Management; Kapitalanlage; Norwegen; Microeconomic Policy: Formulation; Implementation; and Evaluation; Household Saving; Personal Finance; Intertemporal Household Choice; Life Cycle Models and Saving; Portfolio Choice; Investment Decisions; General